The Prickle effect comes from Fabrics made of South American Camelid (Alpaca and Lama) Fibers. Mechanical and/or Genetic Solutions. : A review - Frank, Eduardo; Prieto, Alejandro; Castillo, María; Seghetti Frondizi, Diego; Mamani-Cato, Ruben; Hick, Michel (European Journal of Applied Sciences, 2021)
In this paper we intends to analyze the physical attributes that determine the comfort of fabrics made of South American Camelid fibers (Lama and Alpaca), the effect on their value and their possible mechanical and/or genetic solutions. While emphasis has always been on mean fiber diameter, the fiber frequency exceeding 30 microns has a key role in quality. This is essential for light fabrics, where the effect of prickle plays a critical part in consumer´s choice. Yet the genetic solution of the problem lies in the slow selection response. Dehairing provides an immediate solution, though excessive fiber breakage should be addressed. It is concluded that the textile fiber quality of South American Camelids is promissory if the presence of objectionable fibers is solved, resulting in a tolerable frequency for consumers (<3%). This process could be explored via genetic selection or applying dehairing technology. This implies a true paradigm shift with regard to the classic textile processing of Alpaca and Lama fibers. This would enhance the fiber softness to touch, together with other important features that would render the fiber price more competitive